A randomized controlled trial of NSAIDs or exercise to reduce delayed local pain after influenza vaccination - Housel, L. A.; Beltran, T. A.; Spooner, C.; Collins Jr, L. C.; Ewing, D. F.; Williams, M.; McClenathan, B. M. (The Journal of Allergy and Clinical Immunology, 2020)
We studied the use of pushups and ibuprofen to decrease delayed pain after inactivated influenza vaccine receipt in Service Members. Our results support that pre-emptive interventions are not indicated. Immunogenicity was neither impacted by pushups nor harmed by ibuprofen.